2005
DOI: 10.1016/j.otohns.2004.09.033
|View full text |Cite
|
Sign up to set email alerts
|

OSAS in children: Correlation between endoscopic and polysomnographic findings

Abstract: Adenotonsillar hypertrophy leads to more severe polysomnographic patterns in preschool-age children. More severe apnea is observed in younger children with adenotonsillar hypertrophy than in older ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 15 publications
1
43
0
2
Order By: Relevance
“…The mean age was 8.4 ± 3.99 years (range, 2-15 years), and 50% of the children were male. There were 3 children (7.9%) who were non-apneic, 16 Among the children with obstructive sleep disorder, the symptoms most often reported were snoring and nasal obstruction, which occurred in 75.8 and 73.3%, respectively. Complaints of restless legs during sleep were found in 61.1 and 37.5% reported difficulty in falling sleep.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age was 8.4 ± 3.99 years (range, 2-15 years), and 50% of the children were male. There were 3 children (7.9%) who were non-apneic, 16 Among the children with obstructive sleep disorder, the symptoms most often reported were snoring and nasal obstruction, which occurred in 75.8 and 73.3%, respectively. Complaints of restless legs during sleep were found in 61.1 and 37.5% reported difficulty in falling sleep.…”
Section: Resultsmentioning
confidence: 99%
“…Valera et al showed a greater tendency of OSAHS in preschoolers with the same degree of adenotonsillar obstruction, suggesting the influence of neurological and muscle maturation, as related by Ward and Marcus. (6,16) Stunted growth (weight and height) is most commonly observed in children with OSAHS, who experience an increase in the rate of growth after undergoing tonsillectomy. (25) Decreased production of the growth hormone during fragmented sleep and increased respiratory effort can contribute to the deficit in the growth of these children, (5) as well as to the cardiovascular alterations including pulmonary hypertension and right ventricle dysfunction, which can be potentially avoided by surgically removing the adenoid and tonsillar tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of OSAS is elevated during the early childhood period (3 to 8 years old), and at the same time, adenotonsillar tissue enlargement occurs during this period 18 . Snoring is the most common symptom in 19,20 . Increased sympathetic system, endothelial, and autonomic dysfunctions have been shown in OSAS patients, and choroidal microcirculation, which is maintained by autonomic regulation, may be impaired as a result of one or more of these altered mechanisms 11,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is true that the diagnostic evaluation of pediatric OSAS is rapidly evolving, the current literature would suggest that clinical evaluation poorly predicts the diagnosis of OSAS in children [2][3][4][5][6]. A recent systematic review by Breitzka et al [6] confirms this, quoting an overall positive predictive value of 55.8%, although there was a high degree of heterogeneity between studies.…”
mentioning
confidence: 99%